Caputo–Hadamard Fractional Derivatives of Variable Order. (2nd January 2017) - Almeida, Ricardo
ABSTRACT: In this article, we present three types of Caputo–Hadamard derivatives of variable fractional order and study the relations between them. An approximation formula for each fractional operator, using integer-order derivatives only, is obtained and an estimation for the error is given. At the end, we compare the exact fractional derivative of a concrete example with some numerical approximations.